The Behavior and Postnatal Development in Infant and Juvenile Rats After Ultrasound-Induced Chronic Prenatal Stress - Abramova, Olga; Ushakova, Valeria; Zorkina, Yana; Zubkov, Eugene; Storozheva, Zinaida; Morozova, Anna; Chekhonin, Vladimir (Frontiers in Physiology, 2021)
Fetal development is susceptible to environmental factors. One such factor is exposure to stress during pregnancy. The present study aimed to investigate the effects of chronic prenatal stress on the development and behavior of rat offspring during infancy and juvenile ages. Existing approaches to modeling prenatal stress on animals do not correlate with the main type of stress in pregnant women, namely psychological stress. We used a new stress paradigm in the experiment, namely, stress induced by exposure to variable frequency ultrasound, which acted on pregnant Wistar rats on gestational days 1-21. This type of stress in rodents can be comparable to psychological stress in humans. We assessed physical development, reflex maturation, motor ability development, anxious behavior, response to social novelty, and social play behavior in male and female offspring. Additionally, we investigated maternal behavior and the effect of neonatal handling on behavior. Prenatal stress did not affect postnatal developmental characteristics in rat pups, but prenatally stressed rats had higher body weight in early and adult age than controls. Prenatal exposure to a stressor increased anxiety in the open-field test, changed social preferences in the social novelty test, and impaired social play behavior in males. Neonatal handling reduced anxiety and restored social behavior, but evoked hyperactive behavior in rat pups. Maternal behavior did not change. Our study demonstrated for the first time that exposure to variable frequency ultrasound during pregnancy influences offspring development and impairs behavior, correlating with the effects of other types of stress during pregnancy in rodents. This supports the idea of using this exposure to model prenatal stress.